Comparison of Contract-Relax Stretching Durations on Gastrocnemius Pain in Online Drivers: A Quasi-Experimental Study - Agri, Hergi Rosan; Rahmanto, Safun; Prastowo, Bayu (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Background : Prolonged driving can lead to muscle tension, particularly in the gastrocnemius muscle, which plays a crucial role in ankle stabilization during pedal operation. Contract-Relax Stretching (CRS) is known to be effective in reducing muscle tension through isometric contraction mechanisms. This study aimed to compare the effectiveness of two CRS durations in reducing gastrocnemius muscle pain. Methods : This quasi-experimental study employed a pre-test and post-test design. A total of 34 male four-wheeled online drivers in Jombang were non-randomly assigned into two groups. Group I received CRS intervention for 20 seconds, while Group II received it for 30 seconds. The intervention was administered three times per week for one week. Muscle pain was assessed using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using the Wilcoxon test for within-group comparisons and the Mann–Whitney U test for between-group comparisons. Results : Both groups demonstrated a reduction in VAS scores; however, the changes were not statistically significant. In Group I (20-second CRS), the median VAS score changed from 2 to 3 (P = 0.863), and in Group II (30-second CRS), from 3 to 3 (P = 0.257). The between-group comparison also showed no significant difference (P = 0.427). The majority of participants were aged 36–40 years, and all were male. Conclusion : The difference in CRS duration (20 vs. 30 seconds) did not result in a statistically significant reduction in gastrocnemius muscle pain. External factors such as prolonged sitting duration and traffic conditions may have influenced the outcomes. Keywords : Contract-relax, Driver, Gastrocnemius, Isometric, Muscle pain